2021
DOI: 10.1097/md.0000000000023939
|View full text |Cite
|
Sign up to set email alerts
|

Changes in fasting bile acid profiles after Roux-en-Y gastric bypass and sleeve gastrectomy

Abstract: Background: Bile acid is an essential factor that plays a role in metabolic regulation, but how bile acid is regulated after Roux-en-Y gastric bypass (RYGB) and sleeve gastrectomy (SG) remains unclear. This meta-analysis aimed to investigate changes in the levels of fasting bile acids following RYGB and SG. Methods: A systematic literature search of the PubMed, EMBASE, Cochrane Library and Web of Science databases through July 2020 was performed in acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…Whether improved glycemic control after RYGB is a consequence of slightly better weight control seen in several major studies, or a direct effect of altered gut physiology, is currently an important research topic. A recent meta-analysis showed elevated levels of circulating bile acids after RYGB, but not after SG, possibly due to the anatomical construction of a biliopancreatic limb in RYGB [ 44 ]. Circulating bile acid concentrations were found to be inversely related to HOMA-IR [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Whether improved glycemic control after RYGB is a consequence of slightly better weight control seen in several major studies, or a direct effect of altered gut physiology, is currently an important research topic. A recent meta-analysis showed elevated levels of circulating bile acids after RYGB, but not after SG, possibly due to the anatomical construction of a biliopancreatic limb in RYGB [ 44 ]. Circulating bile acid concentrations were found to be inversely related to HOMA-IR [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The liver plays a central role in determining this condition [35] . Indeed, subjects with severe obesity show an altered hepatic fatty acids trafficking: intra-hepatic fatty acids are shifted towards very-low LDL (VLDL) and triglycerides production rather than oxidative pathways [36] . These mechanisms may explain the different lipid profiles detected in subjects with severe obesity.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, a meta-analysis published by Zhang et al. revealed that after RYGB, the ratio of 12-α-OH: non-12-α-OH bile acids increased instead of decreased in human subjects ( 36 ).…”
Section: Bile Acids and Their Receptorsmentioning
confidence: 99%
“…The findings in VSG are a bit more varied. A study done in rodents reported that total serum bile acids increased after VSG ( 35 ), but a meta-analysis showed that total serum bile acids did not increase in human subjects after VSG ( 36 ). In another study by Chen et al , the authors reported that after human patients received RYGB and VSG, total bile acids in the blood was increased at both three days and three months after surgery ( 37 ).…”
Section: Bile Acids and Their Receptorsmentioning
confidence: 99%